Emergência de plantas daninhas em função da posição da semente e quantidade de palha de cana-de- açúcar - Yamauti, Micheli Satomi [UNESP]; Barroso, Arthur Arrobas Martins [UNESP]; Giancotti, Paulo Roberto Fidelis [UNESP]; Squassoni, Vanessa Luzia [UNESP]; Revolti, Lucas Tadeu Mazza [UNESP]; Alves, Pedro Luis Da Costa Aguiar [UNESP] (My University, 2011)
This work was carried out to evaluate the effects of sugarcane straw density and positions of seeds of Euphorbia heterophylla, Mucuna cinereum, Digitaria nuda and Eleusine indica on emergence and initial development of plants. The experiment were arranged in a completely randomized design, with 15 treatments and four replications, in a factorial arrangement 3 x 5 with a additional control; the first factor was constituted by position of seeds related to the straw (under, between and on) and the second by five quantities of straw (1, 2, 4, 8 e 16 t ha -1) with a control without straw. At 15 days after sowing (DAS) it was realized evaluations of height, dry mass and emergence percentage for E. heterophylla and M. cinereum, and at 28 DAS it was analyzed dry mass and emergence percentage for D nuda e E. indica. Data obtained were submitted to F in variance analysis test and means were compared with Tukey at 5% probability. Emergence and initial development of E. heterophylla e M. cinereum were reduced with increasing of straw and were affected by seed position, but it was not inhibited in none of conditions, indicating aggressiveness of these weeds in sugarcane mechanized harvest conditions. D. nuda and E. indica emergence was not affected by seed position and coverage soil with 8 e 16 t ha -1 of sugarcane straw inhibited its emergence.
Weed emergence in function of seed position and quantity of sugarcane straw
Keywords: Digitaria nuda; Eleusine indica; Euphorbia heterophylla; Germination; Mucuna cinereum; Weed